2015
DOI: 10.6061/clinics/2015(08)10
|View full text |Cite
|
Sign up to set email alerts
|

The association between the rs11196218A/G polymorphism of the TCF7L2 gene and type 2 diabetes in the Chinese Han population: a meta-analysis

Abstract: Transcription factor 7-like 2 has been shown to be associated with type 2 diabetes mellitus in multiple ethnic groups in recent years. In the Chinese Han population in particular, numerous studies have evaluated the association between the rs11196218A/G polymorphism of the transcription factor 7-like 2 gene and type 2 diabetes mellitus. However, the results have been inconsistent, so we performed a meta-analysis to assess the association. Odds ratio and 95% confidence interval values were calculated using a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Table I indicates the basic information of the studies involved in the meta-analysis. The enrolled eight studies included five cohort studies (22)(23)(24)26,27) and three case control studies (20,21,25). The publication year ranged from 1992-2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I indicates the basic information of the studies involved in the meta-analysis. The enrolled eight studies included five cohort studies (22)(23)(24)26,27) and three case control studies (20,21,25). The publication year ranged from 1992-2015.…”
Section: Resultsmentioning
confidence: 99%
“…P<0.05 was considered to represent statistically significant differences. A sensitivity analysis was performed by removing studies one at a time to confirm the robustness of the results (21). Publication bias was assessed by performing the Egger's test (22).…”
Section: Methodsmentioning
confidence: 99%
“…The rapid rise of T2DM prevalence in China is largely believed to be driven by several environmental factors comprising economic development, nutrition transition and changes in lifestyles (Hu et al 2015). However, several convincing T2DM loci have been identified from large-scale genome-wide association studies and meta-analyses in the Han population (Ma et al 2015), suggesting that there may exist genetic predisposition in the Han population to develop T2DM. However, the genetic basis of T2DM and SCZ, especially the inter-relationships of their genetic loci, warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Another similar meta-analysis in the Chinese Han population did not show any association between the TCF7L2 gene rs11196218 A/G polymorphism and T2DM risk. 30 As for GLP1-R gene polymorphism, a study in the European population revealed that rs2268641 in GLP1-R was significantly associated with BMI while rs9380825 is not. 18 , 19 And there have not been studies about the GLP1-R rs761386 variant on obesity yet.…”
Section: Discussionmentioning
confidence: 99%